Usages des TIC et rapports a l’incertitude en situation de catastrophes naturelles - Claire Brossaud (Développement Durable et Territoires)
This article shows how professionnals and disaster victims involved in natural catastrophes in three different areas - Limoges storm in 1999, Abbeville and Bourg-en-Bresse floods in 2001 and 2005 – built a commun risk story with Information and communication technologies (ICT) : Internet, mobiles, data bases, groupware, etc. At first, ICT uses are concretely approached before, during and after the events in a historic context where sciences and technology are growing up to reduce uncertainties of medical and ecological threats. Then, in the second part of this article, a risk culture is supported by socio-cognitive and relationnal competences towards events and their technological holding. At last, we examine ICT place in a collective argumentation and deliberation about the disasters, in particular with specific tolls on our net site corporate http://www.technorisque.net.